Study of the Ion‐Irradiation Behavior of Advanced SiC Fibers by Raman Spectroscopy and Transmission Electron Microscopy. Issue 2 (25th November 2014) - Huguet‐Garcia, Juan; Jankowiak, Aurélien; Miro, Sandrine; Gosset, Dominique; Serruys, Yves; Costantini, Jean‐Marc; Vance, L.
<x xml:space="preserve">Abstract</x> 6H–SiC single crystals and two types of SiC fibers, Hi‐Nicalon type S and Tyranno SA3, have been irradiated with 4‐MeV Au3+ up to 2 × 1015 cm−2 (4 dpa) at room temperature, 100°C and 200°C. These fibers are composed of highly faulted 3C–SiC grains and free intergranular C. Stacking fault linear density and grain size estimations yield, respectively, 0.29 nm−1 and 26–36 nm for the Hi‐Nicalon type S fibers and 0.18 nm−1 and 141–210 nm for the Tyranno SA3 fibers. Both transmission electron microscopy and surface micro‐Raman spectroscopy reveal the complete amorphization of all the samples when irradiated at room temperature and 100°C and a remaining crystallinity when irradiated at 200°C. The latter observations reveal a multi‐band irradiated layer consisting in a partially amorphized band near the surface and an in‐depth amorphous band. Also, nanocrystalline SiC grains with high stacking fault densities can be found embedded in amorphous SiC at the maximum damage zone of the Hi‐Nicalon type S fibers irradiated at 200°C.